D5.1: Recommendations on standardisation, deployment and a research agenda. - Jong, Marjolein de; Persia, Luca; Van der Kloof, Angela; Zoer, Henk Jan; Jorna, Ronald; Kloof, Angela van der; Zoer, Henk Jan; Jordova, Radomira (My University, 2012)
The report describes standardistation issue of ICT and ITS applications, gives information on deployment of applications for safer cycling in European countries, analyzes research in field of cycling, safety and ICT/ITS and gives recommendations into the future. (safecycle)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Informations- und Kommunikationstechnologie; Unfallvermeidung; Radverkehrssicherheit; Standardisierung